beta-glucans in promoting health: Prevention against mutation and cancer - Mantovani, Mario S.; Bellini, Marilanda F. [UNESP]; Angeli, Jose Pedro F.; Oliveira, Rodrigo J.; Silva, Ariane F.; Ribeiro, Lúcia Regina [UNESP] (Elsevier B.V., 2008)
The polysaccharides beta-glucans occur as a principal component of the cellular walls. Some microorganisms, such as yeast and mushrooms, and also cereals such as oats and barley, are of economic interest because they contain large amounts of beta-glucans. These substances stimulate the immune system, modulating humoral and cellular immunity, and thereby have beneficial effect in fighting infections (bacterial, viral, fungal and parasitic). beta-Glucans also exhibit hypocholesterolemic and anticoagulant properties. Recently, they have been demonstrated to be anti-cytotoxic, antimutagenic and anti-tumorogenic, making them promising candidate as pharmacological promoters of health. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: beta-glucans; antimutagenesis; biological activities; chemoprevention; anticarcinogenic